Un italiano de Arezzo en la corte del rey Arturo - López García, Dámaso (Cuadernos de Filología Italiana, 2005)
Petrarch’s presence in English literature cannot be easily defined; such presence has been under or overestimated. Beyond imitations or loans, Petrarch has served a variety of purposes that inspired new topics and forms. If one of the best known features of Petrarchism is taken into account, the characterization of the male lover or the canon of female beauty, then it can be proved that these inspired a kind of poetry radically different from the Petrarchan model in such an author as William Shakespeare.
Keywords: Petrarch; Wyatt; Surrey; Sidney; Shakespeare; influence; English literary history